INFLATION TARGETING AND POLICY DIVERGENCE: AN ANALYSIS OF CENTRAL BANK RESPONSES TO GLOBAL ECONOMIC UNCERTAINTY - M M Munshi; Deshpande, Keerti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Inflation targeting has emerged as a pivotal strategy in central banking, particularly in the face of global economic uncertainty. This study examines the responses of the Reserve Bank of India (RBI), the Federal Reserve System (Fed) in the United States, and the Central Bank of Bangladesh to the challenges posed by fluctuating global economic conditions. By analyzing monetary policy decisions, inflation trends, and economic outcomes in these three countries, the research highlights the divergence in central bank strategies despite a shared objective of maintaining price stability. The findings reveal that while the RBI and the Fed have adopted more flexible approaches, often adjusting inflation targets in response to domestic and international pressures, the Central Bank of Bangladesh has adhered to a more rigid framework. This divergence underscores the complex interplay between global economic forces and domestic policy objectives. The study’s implications suggest that central banks need to continuously adapt their strategies to account for both global uncertainties and domestic economic realities. Future research could explore the long-term effects of these divergent strategies on economic growth and financial stability, as well as investigate how emerging markets can enhance their resilience to external shocks while pursuing inflation targeting.